IL-33-Pretreated Mesenchymal Stem Cells Attenuate Acute Liver Failure by Improving Homing and Polarizing M2 Macrophages - Hui Yuan; Yuwen Li; Zihao Kong; Linya Peng; Jiali Song; Xiaoxue Hou; Wen Zhang; Rui Liu; Tiantong Feng; Chuanlong Zhu (Stem Cells International)
Mesenchymal stem cells (MSCs) are highly effective in the treatment of acute liver failure (ALF). The efficacy of MSCs is closely related to the inflammatory environment. Therefore, we investigated the functional changes of MSCs in response to interleukin-33 (IL-33) stimulation. The results showed that bone marrow mesenchymal stem cells (BMSCs) pretreated with IL-33 had increased CCR2 expression, targeted CCL2 in the injured liver tissue, and improved the migration ability. Under LPS stimulation, the NF-κB pathway of BMDM was activated, and its phenotype polarized to the M1-type, while BMSCs pretreated with IL-33 inhibited the NF-κB pathway and enhanced M2 macrophage polarization. The M2-type macrophages could further inhibit hepatocytes inflammation, reduce hepatocytes apoptosis, and promote hepatocytes repair. These results suggest that IL-33 can enhance the efficacy of BMSCs in ALF and provide a new strategy for cell therapy of liver diseases.